2022
DOI: 10.31980/mosharafa.v11i3.1335
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Berpikir Kreatif Siswa dalam Menyelesaikan Soal berbasis Etnomatematika Tipe Multiple Solutions Task

Abstract: Pentingnya kemampuan berpikir kreatif dalam pembelajaran dicanangkan pada kurikulum 2013. Salah satu tipe soal yang dapat digunakan untuk mengukur kemampuan berpikir kreatif siswa yaitu Multiple Solutions Task (MST). Soal-soal berbasis etnomatematika dapat diujicobakan karena memadukan kebudayaan lokal dengan materi matematika sehingga memotivasi dan meningkatkan kemampuan berpikir kreatif siswa. Penelitian bertujuan mendeskripsikan kemampuan berpikir kreatif siswa dalam menyelesaikan soal MST yang berbasis et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…They indirectly need to keep up-to-date to the latest development of technology (Aminah & Wahyuni, 2018). Also, studying mathematics truly requires creative thinking and computational thinking skill (Faiziyah, Hanan, & Azizah, 2022). Moreover, prospective math teachers are required to think critically and creatively (Afriansyah et al, 2020).…”
Section: Pendahuluanmentioning
confidence: 99%
“…They indirectly need to keep up-to-date to the latest development of technology (Aminah & Wahyuni, 2018). Also, studying mathematics truly requires creative thinking and computational thinking skill (Faiziyah, Hanan, & Azizah, 2022). Moreover, prospective math teachers are required to think critically and creatively (Afriansyah et al, 2020).…”
Section: Pendahuluanmentioning
confidence: 99%
“…Mathematics is part of a culture that has integration in all aspects of human life (Faiziyah et al, 2022;Tandailing, 2013). Learning mathematics teaches logical, systematic, careful, objective e-ISSN: Traditional House of Lampung Kedatun Keagungan…. and open thinking ways of reasoning needed to solve problems in everyday life as well as to face future challenges (Desmayanasari et al, 2018;Faiziyah et al, 2021;Permata et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…D'Ambrosio introduced Ethnomathematics in 1989 to describe a collaboration of mathematics and culture (Sarwoedi et al, 2018;Iqrima, Zulkarnain, & Kamaliyah, 2023) Several ethnomathematical studies with various mathematical concepts have been performed in traditional houses (Nuqthy, Nityana, & Navia, 2022). Ethnomathematics discovery studies of the Cholo Tulung Gagon domicile revealed geometric components and mathematical concepts (Sulistsyani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%